O uso de Você, Ocê e Cê em Belo Horizonte: um estudo em tempo aparente e em tempo real - Edenize Ponzo Peres (2006)
This study seeks to investigate the use of the forms você, ocê and cê in Belo Horizonte during two distinct time periods: 1982 and 2002. Speech data obtained from sociolinguistic interviews conducted in the two different time periods were analyzed, taking six linguistic factors into consideration the syntactic function of each form within phrases, contiguity in relation to the verb, behavior in the construction of topic, the expression of reference, the type of phrase in which the item appears, and focus as well as three extralinguistic factors age (three and five age groups in the 1982 and 2002 corpora respectively), gender and social class (middle and low) of the informants. The central objective of this thesis is to conduct a synchronous and diachronic study of the three forms, describing their behavior at the grammatical as well as social level in accordance with Variation Theory. Of the nine internal and external factors analyzed, some were significant in neither of the two samples, such as contiguity, the type of phrase and the topic, whereas the factors of syntactic function and age were shown to be significant in both of the corpora. As for the other factors, they were shown to be significant in only one corpus. The principal results obtained indicate that a change is occurring in relation to the form cê and there is also a specialization of the forms with respect to the expression of reference, with você being preferable for indefinite references and cê preferable for definite references. On the other hand, marked contexts, such as the object of the verb, the object of the preposition, and focus, presented restrictions on the use of cê, while not impeding its use, which could represent a slow beginning of a change.